1995
DOI: 10.1007/bf01076898
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of phospholipid hydrolysis in vasopressin-stimulated BHK-21 and H9c2 cells

Abstract: The hydrolysis of phospholipids in vasopressin-stimulated baby hamster kidney (BHK)-21 and H9c2 myoblastic cells was investigated. Phosphatidylcholine and phosphatidylethanolamine in these cells were pulse labelled with [3H]glycerol, [3H]myristate, [3H]choline or [3H]ethanolamine, and chased with the non-labelled precursor until linear turnover rates were obtained. When cells labelled with [3H]glycerol or [3H]myristate were stimulated by vasopressin, no significant decrease in the labelling of phosphatidylchol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…In the presence of vasopressin, however, hypertrophy was observed over a broad range of Ca 2 concentrations. In H9c2 cells vasopressin signals multiple events including the activations of PKC, phospholipase C-b, phospholipase A 2 , and the p42 MAP kinase (ERK2) [Tran et al, 1995;Chen and Chen, 1999] all of which are likely to participate in the trophic response. It is equally reasonable to propose that increased expression of GRP78, a chaperone essential to protein translocation, processing and folding, would be required at the early stages of cellular hypertrophy wherein protein synthetic rates rise and cell mass begins to expand.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the presence of vasopressin, however, hypertrophy was observed over a broad range of Ca 2 concentrations. In H9c2 cells vasopressin signals multiple events including the activations of PKC, phospholipase C-b, phospholipase A 2 , and the p42 MAP kinase (ERK2) [Tran et al, 1995;Chen and Chen, 1999] all of which are likely to participate in the trophic response. It is equally reasonable to propose that increased expression of GRP78, a chaperone essential to protein translocation, processing and folding, would be required at the early stages of cellular hypertrophy wherein protein synthetic rates rise and cell mass begins to expand.…”
Section: Discussionmentioning
confidence: 99%
“…The subsequent stimulation of protein synthesis, in contrast, is unaffected by changes in extracellular Ca 2 , depends on gene transcription, is suppressed by a protein kinase C (PKC) pseudosubstrate sequence, and is observed at pM vasopressin concentrations. H9c2 myocytes, like neonatal cardiomyocytes [van der Bent et al, 1994;Aharonovitz et al, 1998;Liu et al, 1999;Xu et al, 1999Xu et al, , 2000] and adult hearts [Fukuzawa et al, 1999;Nakamura et al, 2000], possess all basic features of V1-vasopressin signaling [Tran et al, 1995;Reilly et al, 1998;Chen and Chen, 1999] and undergo hypertrophy in response to the hormone [Brostrom et al, 2000]. Hypertrophy occurs at pM vasopressin concentrations, depends on PKC activity, and precedes full repletion of Ca 2 stores.…”
mentioning
confidence: 99%
“…H9c2 myoblasts, derived from embryonic rat ventricle, were an excellent model system in which to directly test the effects of V 1A R signaling during in vitro stress, as they express cardiac and skeletal isoforms of L-type Ca 21 channels, sarcolemmal ATPase splice variants characteristic of a normal heart and endogenous V 1A R, which respond to AVP with typical Ga q protein-coupled receptor responses (Hescheler et al, 1991;Sipido and Marban, 1991;Hammes et al, 1994;Tran et al, 1995;Reilly et al, 1998;Chen and Chen, 1999;Guo et al, 2012). During the development of the H/R model, we initially found that H/R increased caspase 3/7 activity and decreased cell viability with enhanced robustness over normoxic conditions only under serum-free conditions, whereas the presence of fetal bovine serum protected the cells.…”
Section: Avp Protects H9c2mentioning
confidence: 99%
“…Analysis of the relative amounts of phosphorylated and non-phosphorylated subunit was performed on a Macintosh Quadra 700 computer using the public domain NIH Image program. 2 ] i ) in normal neonatal or H9c2 ventricular myocytes (21)(22)(23)(24)(25) were also examined for the ability to suppress protein synthesis and mobilize Ca 2ϩ stores. Phenylephrine (10 M) and epinephrine (data not shown) elicited marginal responses, whereas angiotensin II and endothelin-1 were ineffective.…”
Section: Camentioning
confidence: 99%
“…The hormone is now appreciated to stimulate lipid metabolism in perfused hearts (47) and H9c2 cells (24), to increase [Ca 2ϩ ] i in cardiomyocytes (39), to potentiate ventricular L-type currents via V1 vascular receptor stimulation (40), and to cause atrial natriuretic factor to be secreted from cardiomyocytes (48). The translational suppression observed in H9c2 cells in response to vasopressin provides additional evidence that the heart is directly targeted by this hormone.…”
Section: S(e)r Ca 2ϩ and Hormonal Regulation Of Translationmentioning
confidence: 99%